2023
DOI: 10.1002/jmv.28976
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection disrupts pulmonary microbiota to induce microglia phenotype shift

Abstract: The lung−brain axis is an emerging biological pathway that is being investigated in relation to microbiome medicine. Increasing evidence suggests that pulmonary viral infections can lead to distinct pathological imprints in the brain, so there is a need to explore and understand this mechanism and find possible interventions. This study used respiratory syncytial virus (RSV) infection in mice as a model to establish the potential lung−brain axis phenomenon. We hypothesized that RSV infection could disrupt the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Substantial research affirms the correlation between respiratory viruses and neurodegenerative diseases. 69,70 For example, an epidemiological study found a link between influenza A virus (IAV) infection and PD onset years later, with IAV detected in the substantia nigra of PD patients. Animal models showed that H1N1 infection induced sustained microglia activation, suggesting chronic inflammation could contribute to neurodegeneration.…”
Section: The Viruses Accelerate Microglia Ageing Through Mitochondria...mentioning
confidence: 99%
See 1 more Smart Citation
“…Substantial research affirms the correlation between respiratory viruses and neurodegenerative diseases. 69,70 For example, an epidemiological study found a link between influenza A virus (IAV) infection and PD onset years later, with IAV detected in the substantia nigra of PD patients. Animal models showed that H1N1 infection induced sustained microglia activation, suggesting chronic inflammation could contribute to neurodegeneration.…”
Section: The Viruses Accelerate Microglia Ageing Through Mitochondria...mentioning
confidence: 99%
“…Drugs targeting microtubule stability, kinesin motors, or suppressing mitochondrial ROS production effectively inhibit RSV production, as shown in a mouse model where they also alleviated virus-induced lung inflammation. 70,86 A preliminary study using a knockout (KO) cell line deficient in mitochondrial complex I activity suggested that host cell mitochondria are crucial targets for RSV. Specifically, mitochondrial complex I modulates respiration and increases mtROS levels, contributing to RSV infection.…”
Section: Respiratory Syncytial Virusmentioning
confidence: 99%